Observational Study on Treating Overweight due to Phlegm and Dampness by Using Abdominal Application Method - Ong, Sze Wei (2015)
Overweight is known to be the worldwide health problems which increased the risk of co-morbidities such as metabolic syndrome and cardiovascular diseases. Although the dietary or lifestyle changes must be personalized, controlled energy intake with a moderately elevated protein intake may represent an effective and practical weight-loss strategy. But using the abdominal application method is a way to reduce the fat especially abdominal fat. Traditional Chinese Medicine not only has obvious advantages and significant effect on overweight, but also has little toxic, little side effects and highly secure, which makes it welcomed by public. Traditional Chinese Medicine treats the overweight and obesity by regulating the functions of Zang-Fu organs and people’s constitutions. The purpose of the experiment was to investigate the effect of the weight reducing formula on reducing body weight and waist circumference by using abdominal application method. Thus, this project is to observe the dermal absorption of raw Traditional Chinese Medicine herbs and to understand the external application method. Furthermore, it is to promote the treatment methods of medicated dressing on acupuncture points. The result of this experiment shown that it is helpful to reduce the waist circumference in certain cases.